2017
DOI: 10.1007/s00239-017-9792-x
|View full text |Cite
|
Sign up to set email alerts
|

Plastome-Wide Nucleotide Substitution Rates Reveal Accelerated Rates in Papilionoideae and Correlations with Genome Features Across Legume Subfamilies

Abstract: This study represents the most comprehensive plastome-wide comparison of nucleotide substitution rates across the three subfamilies of Fabaceae: Caesalpinioideae, Mimosoideae, and Papilionoideae. Caesalpinioid and mimosoid legumes have large, unrearranged plastomes compared with papilionoids, which exhibit varying levels of rearrangement including the loss of the inverted repeat (IR) in the IR-lacking clade (IRLC). Using 71 genes common to 39 legume taxa representing all the three subfamilies, we show that pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 91 publications
3
47
0
Order By: Relevance
“…1990 ). In addition, the rates of nucleotide substitution in genes of the IRLC-papilionoids are generally higher than those found in the IR-containing papilionoids ( Schwarz et al. 2017 ).…”
Section: Discussionmentioning
confidence: 78%
“…1990 ). In addition, the rates of nucleotide substitution in genes of the IRLC-papilionoids are generally higher than those found in the IR-containing papilionoids ( Schwarz et al. 2017 ).…”
Section: Discussionmentioning
confidence: 78%
“…Estimating nucleotide substitution rates among different genes and different functional groups provided insight into the diverse selection regimes acting on plastomes evolution (e.g. [ 16 , 20 , 22 ]). In Poaceae [ 34 ] and Geraniaceae [ 17 ], it has been reported that genes encoding subunits involved in photosynthetic processes, such as NAD(P)H dehydrogenase (NDH), ATP synthase (ATP), photosystems I and II (PSA and PSB), and cytochrome b6f complex (PET), exhibit relatively lower nucleotide substitution rates than other functional groups of genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have been previously documented, such as RPL and RPS genes were shown to be highly accelerated in Geraniaceae [ 20 , 28 ] and RPO genes in Annonaceae, Passifloraceae and Geraniaceae [ 52 ]. In addition , accD, clpP, ycf1 , and ycf2 had the most accelerated rates [ 22 ] as detected in plastomes of Silene (Caryophyllaceae), and clpP and ycf1 were found to have the highest d N values among genes in legumes [ 16 ]. In the present study, ycf1 and matK had the highest d N value, and ycf2 had the highest d N /d S value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chloroplast genes have highly heterogeneous substitution rates across legumes, leading to a wellresolved topology in core Papilionoideae but poor resolution in other lineages, particularly Caesalpinioideae (Figs 2C & S1-4). It has long been known that there is significant variation in rates of chloroplast sequence evolution among plant lineages (Bousquet et al, 1992) and previous analyses of single chloroplast genes (Lavin et al, 2005) and legume chloroplast genomes (Dugas et al, 2015;Schwarz et al, 2017;Wang et al, 2018) have suggested substantial variation in rates of molecular evolution among legume lineages. Because branch model Dn/Ds ratio tests do not provide evidence for different selective forces on photosynthesis genes across legumes, this pattern may rather be related to life-history strategies in the 50Kb-inversion clade, which includes many herbaceous plants of short stature (Lanfear et al, 2013) and shorter generation times (Smith & Donoghue, 2008), especially in the vicioid clade where the highest rates are found (Fig.…”
Section: Discussionmentioning
confidence: 99%